Expert opinion for use of faecal calprotectin in diagnosis and monitoring of inflammatory bowel disease in daily clinical practice. Issue 8 (October 2018) - Reenaers, Catherine; Bossuyt, Peter; Hindryckx, Pieter; Vanpoucke, Hilde; Cremer, Anneline; Baert, Filip
Background: Despite many publications regarding the role of faecal calprotectin (FC) in inflammatory bowel disease (IBD), clear recommendations for its use in clinical practice are currently lacking in the literature. Aim: The aim of this article is to provide practical guidance for clinicians for the use of FC in the detection and management of patients with IBD. Methods: All relevant publications were analysed and practical statements were proposed based on a Delphi consensus approach. Results: Different commercial assays have been developed but international standardisation is lacking. FC can help in the diagnosis process of IBD. In IBD, FC can predict response to therapy, detect subclinical inflammation and help to drive treatment decisions to achieve better endoscopic and clinical outcomes. After Crohn's surgery FC can identify patients with early endoscopic recurrence. Conclusion: Although major therapeutic changes should not be based on FC alone, FC is a valuable tool to optimise the care for IBD patients.